2000
DOI: 10.1200/jco.2000.18.3.537
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Bone Marrow Versus Lenograstim-Primed Blood Cell Allogeneic Transplantation in Patients With Early-Stage Leukemia: A Report From the Société Française de Greffe de Moelle

Abstract: This study establishes that allogeneic BCT results in quicker hematologic recovery but is associated with a higher occurrence of chronic graft-versus-host disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
294
0
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(321 citation statements)
references
References 35 publications
19
294
0
8
Order By: Relevance
“…Most of the published studies showed that allo-SCT with the use of PBSC as opposed to BM, is associated with a similar rate of acute GVHD (aGVHD), but an increased incidence of cGVHD. [1][2][3][4][5][6][7] Moreover, in accordance with these data, some studies also show better OS and disease-free survival (DFS) among patients with advanced leukemia after allogeneic PBSC transplantation (allo-PBSC). 4,8 This association has been explained mostly by the decreased incidence of relapse in patients with GVHD.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Most of the published studies showed that allo-SCT with the use of PBSC as opposed to BM, is associated with a similar rate of acute GVHD (aGVHD), but an increased incidence of cGVHD. [1][2][3][4][5][6][7] Moreover, in accordance with these data, some studies also show better OS and disease-free survival (DFS) among patients with advanced leukemia after allogeneic PBSC transplantation (allo-PBSC). 4,8 This association has been explained mostly by the decreased incidence of relapse in patients with GVHD.…”
Section: Introductionmentioning
confidence: 53%
“…On the contrary, the vast majority of the published studies showed increased rates of cGVHD with the use of PBSC in comparison with BM grafts. [1][2][3][4][5][6][7] The influence of allo-PBSC on long-term survival remains more controversial and is mainly dependent on the disease status before transplantation. Some studies reported a favorable outcome after myeloablative allo-PBSC for patients with advanced myeloid leukemias, mostly because of decreased RRs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the incidence of grades 2-4 acute GVHD observed in the G-CSF group in this trial (49%) is clearly in line with rates (21-64%) reported in the PBPC arms of several randomized trials. [1][2][3][4][5][6][7] The lack of any grade 3-4 acute GVHD in the GM-CSF group is noteworthy given the large proportion of patients transplanted for high-risk disease.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Nevertheless, in only a minority of the randomized comparative trials did this translate into an overall survival advantage and some studies suggested the use of G-CSF mobilized PBPC was associated with a greater risk of either acute or chronic graft-versus-host disease (GVHD), or both. 6,[8][9][10] In two recent retrospective studies in patients with aplastic anemia or children with leukemia performed by the International Bone Marrow Transplant Registry, transplantation of G-CSF mobilized PBPC was associated with higher rates of GVHD.…”
Section: Csf; G-csfmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] In the setting of HLA-matched sibling donor (MSD) transplantation, several randomized trials showed that PBSC resulted in faster engraftment, but increased the risk of chronic GVHD compared with BM. [11][12][13][14][15][16][17][18][19] In addition, some studies showed a decreased rate of relapse and better survival with PBSC, especially in patients with more advanced hematologic malignancies. 15,17,18 However, these results may not be applicable to unrelated donor (URD) transplants, given the greater risk of GVHD owing to their greater genetic diversity.…”
Section: Introductionmentioning
confidence: 99%